Editorial: Technologies in smallholder poultry development: characterization, utilization, conservation, improvement, waste management, and disease control volume II - Yakubu, A.; Bamidele, Oladeji; Thiruvenkadan, A.K.; Okpeku, M.; Çelik, S. (Frontiers Media, 2024)
Smallholder poultry production systems (SPPS) are very important, especially for low-input farming systems (Bamidele et al., 2023). The SPPS contribute substantially to income generation, job creation, empowerment of women and youths, and improvement in the nutrition and health of farmers, especially in low-and middle-income countries. Despite these benefits, the output derived from poultry species from smallholdings is very low amidst increasing demand for animal-sourced protein as well as the rapid global growth of the human population. Therefore, there is a dire need to embrace modern technologies to conserve and improve poultry genetic resources to guarantee maximum production and productivity of the birds (Hu et al., 2022; Birhanu et al., 2023; Perini et al., 2023; Olaniyan et al., 2024; Zhou et al., 2024).